Democratic Republic of Sao Tome and Principe : Debt Relief at the Completion Point Under the Heavily Indebted Poor Countries Initiative and Under the Multilateral Debt Relief Initiative. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This paper examines the consideration of the Democratic Republic of Sao Tome and Principe's debt relief at the completion point under the enhanced Initiative for Heavily Indebted Poor Countries and Debt Relief under the Multilateral Debt Relief Initiative. Lower-than-projected export receipts largely owing to drought conditions and lower-than-expected tourism receipts, changes in cross-currency exchange rates, and variations in discount rates have been all unambiguously exogenous and outside the control of the authorities. There is need for continued fiscal prudence, policies to support broad-based growth and export diversification, continued donor support, and prudent debt management.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet